Minimizing Adverse Environmental Impact: How Murky the Waters - Reed W. Super; David K. Gordon (The Scientific World Journal)
The withdrawal of water from the nation’s waterways to cool industrial facilities kills billions of adult, juvenile, and larval fish each year. U.S. Environmental Protection Agency (EPA) promulgation of categorical rules defining the best technology available to minimize adverse environmental impact (AEI) could standardize and improve the control of such mortality. However, in an attempt to avoid compliance costs, industry has seized on the statutory phrase “adverse environmental impact” to propose significant procedural and substantive hurdles and layers of uncertainty in the permitting of cooling-water intakes under the Clean Water Act. These include, among other things, a requirement to prove that a particular facility threatens the sustainability of an aquatic population as a prerequisite to regulation. Such claims have no foundation in science, law, or the English language. Any nontrivial aquatic mortality constitutes AEI, as the EPA and several state and federal regulatory agencies have properly acknowledged. The focus of scientists, lawyers, regulators, permit applicants, and other interested parties should not be on defining AEI, but rather on minimizing AEI, which requires minimization of impingement and entrainment.